Monitoring agriculture sector performance, growth and poverty trends in Mozambique - Chilonda, Pius; Xavier, Victorino; Luciano, Lucia; Chamusso, Adriano; Zikhali, Precious; Faria, Angela; Govereh, Jones; Manussa, Sofia; Acubar, Baptista; Musaba, Emmanuel; Osvaldo, Luis; Alage, Noé; et al. (International Water Management Institute, 2011)
This report assesses the performance of the agriculture sector in Mozambique. It focuses on analysis of agricultural investment, growth, trade, poverty and hunger trends, and the progress made by Mozambique towards attaining the targets of the African Union's (AU) Comprehensive Africa Agriculture Development Programme (CAADP) and The Southern African Development Community's (SADC) Regional Indicative Strategic Development Plan (RISDP). The monitoring of the sector's performance contributes towards, and promotes, the culture of evidence-based development planning. Regional commitments such as CAADP and national strategies such as the Strategic Plan for the Development of the Agricultural Sector (PEDSA) have developed monitoring and evaluation (M&E) frameworks. This trends report signals the Ministry of Agriculture's (MINAG) interest and effort to implement these frameworks with the support of the Mozambique Strategic Analysis and Knowledge Support System (MozSAKSS) funded by the Swedish International Development Agency (SIDA).